Enhanced Deep-Inspiration Breath Hold Superior to High-Frequency Percussive Ventilation for Respiratory Motion Mitigation: A Physiology-Driven, MRI-Guided Assessment Toward Optimized Lung Cancer Treatment With Proton Therapy - Emert, Frank; Missimer, John; Eichenberger, Philipp A.; Walser, Marc; Gmür, Celina; Lomax, Antony J.; Weber, Damien C.; Spengler, Christina M. (Frontiers in Oncology, 2021)
Background: To safely treat lung tumors using particle radiation therapy (PRT), motion-mitigation strategies are of critical importance to ensure precise irradiation. Therefore, we compared applicability, effectiveness, reproducibility and subjects' acceptance of enhanced deep-inspiration breath hold (eDIBH) with high-frequency percussive-ventilation (HFPV) by MRI assessment within one month. Methods: Twenty-one healthy subjects [12 males/9 females; age: 49.5±5.8 years; BMI: 24.7±3.3 kg·m-2] performed two 1.5T MRI scans in 4 visits at weekly intervals under eDIBH and HFPV conditions, accompanied by daily, home-based breath-hold training and spirometric assessments over a 3-week period. eDIBH consisted of 8-min 100%-O2-breathing (3min resting ventilation, 5min controlled hyperventilation) prior to breath hold. HFPV was set at 200-250 pulses·min-1 and 0.8-1.2 bar. Subjects' acceptance and preference were evaluated by questionnaire. To quantify inter- and intra-fractional changes, a lung-distance-metric representing lung topography was computed for ten reference points: a motion-invariant spinal cord and nine lung structure contours (LSCs: apex, carina, diaphragm and six vessels as tumor surrogates distributed equally across the lung). To parameterize individual LSC localizability, measures of their spatial variabilities were introduced and lung volumes calculated by automated MRI analysis. Results: eDIBH increased breath-hold duration by >100% up to 173±73s at Visit 1, and to 217±67s after 3 weeks of home-based training at Visit 4 (p<0.001). Measures of vital capacity and lung volume remained constant over the 3-week-period. Two vessels in the lower lung segment and the diaphragm yielded a 2-3-fold improved positional stability with eDIBH, whereby absolute distance variability was significantly smaller for 5 LSCs. ≥70% of subjects showed significantly better intra-fractional lung motion-mitigation under reproducible conditions with eDIBH compared to HFPV with smaller ranges most apparent in the anterior-posterior and cranial-caudal directions. ~80% of subjects preferred eDIBH over HFPV, with ‘less discomfort’ named as most frequent reason. Conclusions: Both, eDIBH and HFPV were well tolerated. eDIBH-duration was long enough to allow for potential PRT. Variability in lung volume was smaller and position of lung structures more precise with eDIBH. Subjects preferred eDIBH over HFPV. Thus, eDIBH is a very promising tool for lung tumor therapy with PRT and further investigation of its applicability in patients is warranted.